Chechu Álava: las venus de la libertad y del deseo - del Pilar García Buendía, María (Dialogoi. Rivista di studi comparatistici, 2020)
In this paper, I intend to set out the feminist discourse as an aesthetic stance taking of Spanish painter Chechu Álava entailed in her works El placer de la Venus de Urbino. Elogio de la masturbación, 2016 and Venus, 2017. To do so, I will show how it is encoded in the way these two works relate to one another and the intertextual relation they maintain with their referential Venere di Urbino (1538), by Tiziano and the contributions on the archetype of Venus painted by Lucas Cranach, The Elder (Venus, 1532) and Velázquez (La venus del espejo, 1647), on one side or the Modern representations carried out by Goya (La maja desnuda (1797-1800) or Manet (Olympia, 1863).